2013
DOI: 10.3402/ijch.v72i0.20992
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of increasingHaemophilus influenzaenon-b infection in Australian Aboriginal children

Abstract: BackgroundHigh, or increasing, rates of invasive Haemophilus influenzae (Hi) type a disease have been reported from North American native children from circumpolar regions, raising the question of serotype replacement being driven by vaccination against Hi type b (Hib). Indigenous Australians from remote areas had high rates of invasive Hib disease in the past, comparable to those in North American Indigenous populations.ObjectiveEvaluate incidence rates of invasive Hi (overall and by serotype) in Indigenous A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 13 publications
(14 reference statements)
2
19
0
Order By: Relevance
“…Because comparative pre-vaccine data for the incidence of encapsulated non-b strains was unavailable, the phenomenon of strain replacement could not be adequately assessed. A recent study by Menzies et al demonstrated no increasing trend in Hia or NTHi in the Indigenous population in South Australia and Northern Territory and overall post-vaccination rates of invasive encapsulated and non-typable disease were lower than pre-vaccination rates in that population [35]. The number of notified cases and rates of Hib Australia-wide plummeted markedly following Hib vaccine introduction [10].…”
Section: Discussionmentioning
confidence: 99%
“…Because comparative pre-vaccine data for the incidence of encapsulated non-b strains was unavailable, the phenomenon of strain replacement could not be adequately assessed. A recent study by Menzies et al demonstrated no increasing trend in Hia or NTHi in the Indigenous population in South Australia and Northern Territory and overall post-vaccination rates of invasive encapsulated and non-typable disease were lower than pre-vaccination rates in that population [35]. The number of notified cases and rates of Hib Australia-wide plummeted markedly following Hib vaccine introduction [10].…”
Section: Discussionmentioning
confidence: 99%
“…9 However, a recent surveillance study in Australia has failed to demonstrate an increase in invasive Hia since the introduction of the Hib vaccine. 10 An epidemiological calculation of invasive H. influenzae disease in the USA concluded that although the incidence of Hib has fallen in American Indians and native Alaskan children since the introduction of the vaccine, invasive disease has not been replaced by non-Hib serotypes. 11 Our patient responded well to timely surgical intervention and antibiotics, with a significant clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…An unexpectedly large proportion of invasive childhood infections caused by serotype a was recently reported from several Canadian provinces (205,230) and among Alaska Native children (231). There is no evidence of substantial replacement disease with non-b serotypes in young children in the United States (232) or of increases of non-b infection in Australian indigenous children (233).…”
Section: Haemophilus Influenzae In the Post-hib-vaccine Eramentioning
confidence: 99%